Europe : a natural history - Flannery, Tim F. (Tim Fridtjof), 1956-; Boitani, Luigi ([London] : Allen Lane, an imprint of Penguin Books, 2018)
A place of exceptional diversity, rapid change, and high energy, for the past 100 million years Europe has literally been at the crossroads of the world. By virtue of its geology and geography, evolution in Europe proceeds faster than elsewhere. The continent has absorbed wave after wave of immigrant species over the millennia, taking them in, transforming them, and sometimes hybridizing them. Flannery's exploration of the nature of Europe reveals a compelling intellectual drama, with a cast of heroic researchers--of whom Tim Flannery is the most recent--whose discoveries have changed our understanding of life itself --
Introduction -- I. The tropical archipelago : 100-34 million years ago -- II. Becoming continental : 34-2.6 million years ago -- III. Ice ages : 2.6 million-38,000 years ago -- IV. Human Europe : 38,000 years ago to the future.
Includes bibliographical references (pages 319-346) and index.
Keywords: Natural history -- Europe